1999
DOI: 10.1364/ao.38.000724
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient optical detection of surface-generated fluorescence

Abstract: We present a theoretical study of a new highly efficient system for optical light collection, designed for ultrasensitive fluorescence detection of surface-bound molecules. The main core of the system is a paraboloid glass segment acting as a mirror for collecting the fluorescence. A special feature of the system is its ability to sample not only fluorescence that is emitted below the angle of total internal reflection (the critical angle) but also particularly the light above the critical angle. As shown, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 161 publications
(105 citation statements)
references
References 8 publications
1
104
0
Order By: Relevance
“…The optical set-up is inverse to that of TIRF with an excitation beam illuminating the sample perpendicularly and a collection of fluorescence light emitted into the supercritical angle of the substrate using a parabolic mirror objective. The SAF technology itself (2000) [238,239], a SAF sensing instrument (2003) [240], and also a SAF imaging instrument (2007) [241,242] were recently developed. The strength of the SAF technique to study protein adsorption phenomena was demonstrated in some recent publications [44,102,118,187] or TIRF set-ups and, more recently, also with the SAF optics [244].…”
Section: Fluorescence Detection Techniquesmentioning
confidence: 99%
“…The optical set-up is inverse to that of TIRF with an excitation beam illuminating the sample perpendicularly and a collection of fluorescence light emitted into the supercritical angle of the substrate using a parabolic mirror objective. The SAF technology itself (2000) [238,239], a SAF sensing instrument (2003) [240], and also a SAF imaging instrument (2007) [241,242] were recently developed. The strength of the SAF technique to study protein adsorption phenomena was demonstrated in some recent publications [44,102,118,187] or TIRF set-ups and, more recently, also with the SAF optics [244].…”
Section: Fluorescence Detection Techniquesmentioning
confidence: 99%
“…In the work presented here, this disadvantage was overcome using super critical angle fluorescence (SAF) microscopy, which excludes all fluorescence except that arising from within ~ 200 nm of the surface. 32,33 Thus the adsorption of α−Syn can be studied in real time with no need for washing steps to remove unbound protein from the bulk solution.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Furthermore, it has been shown that the fluorescence lifetime strongly depends on the position and orientation of the SM with respect to the boundaries of the film, an effect known as the influence of the electromagnetic boundary conditions (EBC). [6][7][8][9][10][11][12][13] This effect is especially important in very thin polymer films (<30 nm). Therefore, several groups have devoted efforts to determine the 3D orientation of a SM in thin polymer films.…”
mentioning
confidence: 99%